2015
DOI: 10.1007/s00772-015-0060-3
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound diagnostics of renal artery stenosis

Abstract: Background and purposeAs a non-invasive, side effect-free and cost-effective method, ultrasonography represents the method of choice for the diagnosis of renal artery stenosis. Four different criteria in total, including two direct criteria in peak systolic velocity (PSV) and renal aortic ratio (RAR) and two indirect criteria in resistance index (RI) and acceleration time (AT) for the measurement of relevant renal artery stenosis are described, each demonstrating highly variable accuracy in studies. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 50 publications
1
15
0
2
Order By: Relevance
“…A previous study also used CEUS for the diagnosis of renal artery stenosis and showed good results. They found that the sensitivity, specificity, and accuracy of CEUS were similar to selective angiography [ 23 ]. Our study investigated the diagnostic value of CEUS in renal artery stenosis using DSA as the gold standard which is superior to selective angiography that was used in the previous study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study also used CEUS for the diagnosis of renal artery stenosis and showed good results. They found that the sensitivity, specificity, and accuracy of CEUS were similar to selective angiography [ 23 ]. Our study investigated the diagnostic value of CEUS in renal artery stenosis using DSA as the gold standard which is superior to selective angiography that was used in the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the clinical application of CTA and MRA is limited in some particular cases. Although DUS has been widely used as an initial imaging modality for the diagnosis of renal artery stenosis [ 21 , 22 ], factors such as depth, obesity, complex anatomy, bowl gas, and operator dependent may limit the use of the Doppler ultrasound [ 23 ]. More recently, the use of CEUS in the detection of renal artery stenosis has raised the attention of many researchers [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…When U, HE4, and RI were combined for detection, the sensitivity was 91%, and when the U, PI, ER and HE4 were combined, the RI joint detection sensitivity was 92.7%. 24 The combination improves the detection accuracy and decreases the false positivity rate. 25 Our retrospective study is the first to increase the sensitivity of the early detection and differential diagnosis of EOC with TVCEUS combined with HE4 and RI.…”
Section: Discussionmentioning
confidence: 99%
“…Renal color Doppler ultrasonography is a useful noninvasive physiological examination for the assessment and follow-up of patients with chronic kidney diseases (CKD) [ 1 – 4 ]. In addition to kidney size, routine ultrasonic indices—end-diastolic velocity (EDV), peak systolic velocity (PSV), and resistive index (RI)—are usually measured in multiple regions from the central to peripheral kidney [ 3 , 5 ]. Because renal color Doppler ultrasonography was introduced only in the past few decades, its clinical usefulness and guidelines for interpretation are still being determined.…”
Section: Introductionmentioning
confidence: 99%